PERLINDUNGAN HUKUM BAGI BIDAN DALAM PROGRAM PELAYANAN KONTRASEPSI KELUARGA BERENCANA YANG BERKEADILAN - Putri Wardhani; Ahmad Wahid (Smart Law Journal, 2023)
Maternal Mortality and Infant Mortality are one of the main targets of the 2015-2019 RPJMN. One of the causes of the high maternal and infant mortality rate is pregnant women with condition 4 too. The government, through BKKBN, launched a Family Planning Service Program or the use of Contraceptives. Midwives, should only provide short-term contraceptive services in the form of giving Pills, condoms and injections. The authority of midwives in the provision of long-term contraceptives, such as IUD and implants, is an authority that is an assignment from the government. The problem in this study is How is the legal protection for midwives in the family planning contraceptive service program that is equitable?. The method used is qualitatively descriptive and matches the results in the field with government regulations related to obstetric services. The authority under the Law is delegative, referring to how the protection is provided if a problem arises, Long-term contraception still has a post-installation risk. If the problem arises, the midwife is expected to have the right protection. Advice for the community and midwives to be able to better understand the current authority of midwives, not only based on past traditions, IBI can increase knowledge related to legal aspects of midwifery services so as to prevent violations of authority. The government is expected to review regulations that limit basic midwifery services in the community.